Inconvenient friendship: How successful cocaine dealers manage social obligations. Issue 2 (12th May 2021) - Crawford, David
Abstract : Based on life history interviews with successfully retired drug dealers, this article examines opportunities and challenges in the suburban underground economy. "Friendship" is key. Suburban drug dealing occurs exclusively through networks of friends, kin, and the acquaintances thereof. Friends are functionally necessary for the suburban illegal drug business but also economically inconvenient in that they require sharing drugs, spending time, "hanging out, " and "partying." Friends represent "transaction costs" in conventional economic terms. The ambivalence produced by this, in profiting from friends and mixing sociality and commerce, is best understood via insights from economic anthropology, preeminently Marcel Mauss. For Mauss, gifts and self‐interest, generosity and profit, are, and ought to be, conceptually inseparable. Dealers vividly demonstrate this entanglement.